Physical Functioning Not Daily Energy Expenditure Differs In Older Adults Relative To Physical Activity Format...2021 ACSM Annual Meeting & World Congresses [Virtual], June 1 -5, 2021 - Turner, Michael J.; Wilcox, Ali K. (Medicine & Science in Sports & Exercise)
PURPOSE: Older adults are known to gain the benefits of improved cognition, reduced risk of falls, and decreased mortality when participating in regular physical activity. Nearly sixty percent of older adults suggest they are not involved with regular physical activity or exercise, but those who are regularly active participate in different structured and unstructured programming options. Our investigation studied the influence of different physical activity options on perceived quality of life, step counts, and sleep behaviors in the older adult population. METHODS: Forty-five older adult volunteers answered a questionnaire that asked "Do you exercise?" If answered "Yes", then participants were asked "Is it structured (SE-Structured Exercise) or independent (IE-Independent Exercise)?". If answered "No", then participants were asked "Do you lead an active lifestyle (AL-Active Lifestyle) or not (C-Control)?" Nine men and 36 women participated in the current study, with group mean ages (±SD) of SE: 73.9±6.6yrs (n=13), IE: 76.5±6.1yrs (n=13), AL: 79.9±9.6yrs (n=10), C: 69.8±5.8yrs (n=9). Perceived health status and sleep quality were assessed with the SF-36 & PSQI, respectively, while daily energy expenditure and sleep quality were measured through a wrist worn Fitbit Charge HR for seven days. RESULTS: Groups were similar in height and weight (p>0.05), but SE and C were found to be younger (p=0.02) than the IE and AL groups. No group differences were observed for energy expenditure, sleep quality, or sleep efficiency (p>0.05). Pain (p= 0.002) and physical functioning (p=0.01) were lesser in the AL group compared to the remaining groups. Perceived health (p= 0.07) and daily step count (p= 0.07) trended towards group differences but were not statistically significant. CONCLUSIONS: Physical functioning and daily pain were influenced by physical activity programming with older adults, yet daily step counts and energy expenditure was found to not be influenced by type of activity programming with older adults.